Fee-Based Electronic Information Services and Effective Service Delivery by Federal University Libraries in Nigeria - Nuhu, Ahmed Khadiy; Aliyu, Jafaru Shinkafi (Ghana Library Journal, 2022)
The study investigated fee-based electronic information services offered in Nigerian federal university libraries, their effects on library services, challenges faced by libraries that implemented the services and possible solutions to address the challenges. A descriptive survey research design using stratified random sampling was used for the study. The population of the study was Nigerian federal university libraries. The population size for the study is 116. Using Krejcie and Morgan’s table, a total of ninety-two (92) professional librarians were sampled. Google form was used for data collection. Out of 92, 87 (80.04%) librarians responded to the questionnaire. The results obtained from the analysis were presented in tables using frequency and the mean by Statistical Package for the Social Sciences (SPSS, version 25). The findings of the study revealed that the only university of Lagos in federal university libraries that partially implemented two services (internet access and laptop lending). The research also revealed that in the university of Lagos, the services enable the library to generate more income, it increases library users’ patronage among others. The challenges faced by the University of Lagos while rendering the fee-based services include poor planning, the problem of pricing policy and negative perception of fee-based services by the patrons among others. The study concluded that Nigerian federal university libraries have not yet implemented fee-based electronic information services to their full course. The study recommended among others that seminars and conferences should be organized to enlighten the stakeholders of Nigerian federal university libraries on the benefits of fee-based electronic information services for effective library service delivery.